THE SURVIVAL OF TRANSPLANTED CORAL ON PYRAMID-SHAPED FISH SHELTER ON THE COASTAL WATERS OF KELAPA AND HARAPAN ISLANDS, KEPULAUAN SERIBU, JAKARTA - Ofri Johan (Indonesian Aquaculture Journal, 2012)
Research was carried out in August 2008 at two sites within Marine Protected Areas (MPA) in Kelapa and Harapan Islands of Seribu Islands, Indonesia. The purpose of this research was to compare the mortality rate of coral transplanted on the upper and base of pyramid-shaped concrete fish shelters. Fish shelters were placed on the seabed of Kelapa Island which is characterized by sandy seabed and Harapan Island which is characterized by silt. Both sites are within Marine Protected Areas. The survey recorded mortality rate of transplanted coral and percentage of live coral coverage. The research also sampled fish populations within the MPA sites and pyramid areas so that the two sites can be compared for their fish biodiversity. The data were analyzed by using T-Test Student of SPSS 11.5 computer program to compare between two locations, and upper and base of transplanted position. After one year, the average mortality rate among transplanted coral species in Kelapa Island was 34%. However, the mortality rate of transplanted coral in Harapan Island was slightly higher than in Kelapa Island: 42%. The transplanted coral at the top of the fish shelter had higher survival rate (39%) compared to the base of the fish shelter (24%). Fish populations in Kelapa Island consisted of 1,119 individuals from 35 species. This was much higher than in Harapan Island where the research found only 655 individuals from 27 species. Fish populations found around the fish  shelter area in Kelapa Island consisted of 125 individuals from 25 species. This was lower than the fish population in Harapan Island, where 206 individuals from 23 species were recorded.